Sex differences in metabolic regulation by Gi/o-coupled receptor modulation of exocytosis - Young, Montana; Ceddia, Ryan P.; Thompson-Gray, Analisa; Reyes, David; Cassada, Jackson B.; Ayala, Julio E.; McGuinness, Owen P.; Collins, Sheila; Hamm, Heidi E. (Frontiers in Pharmacology, 2025)
BackgroundPresynaptic Gi/o coupled GPCRs can act as negative feedback regulators of neurotransmitter release via Gβγ effector modulation through two mechanisms: decreased calcium influx and direct inhibition of membrane fusion by soluble N-ethylmaleimide—sensitive factor attachment protein (SNAP) receptor (SNARE). Previously, we discovered that truncation of the last three C-terminal amino acids of SNAP25 (SNAP25Δ3) prevents Gβγ-SNARE interaction, effectively removing the braking mechanism on neurotransmitter release. We have demonstrated enhanced metabolic protection in male SNAP25Δ3/Δ3 mice housed at room temperature (22°C), including increased adipose tissue beiging and glucose uptake and enhanced insulin sensitivity, rendering them resistant to diet-induced obesity (DIO). When male SNAP25Δ3/Δ3 mice were housed at thermoneutrality (30°C), all metabolic protection was abolished, suggesting sympathetic tone is important for the phenotypes.MethodsWe housed male and female mice at either standard room temperature (21°C) or at thermoneutrality (30°C) and fed them a high fat diet (HFD) for 8 weeks. Glucose tolerance tests were performed before and after the 8 weeks of HFD along with body composition analyses. Organs were then dissected for mass analysis as well as immunohistochemistry. Additionally, we ovariectomized female mice to investigate the role of sex hormones in our phenotypes. Finally, we housed mice in Sable Promethion chambers at various environmental temperatures to investigate the effect of environmental temperature on basal metabolic rates.ResultsWe found SNAP25Δ3/Δ3 female mice exhibited the same metabolic protection at RT (22°C) and displayed enhanced metabolic protection from DIO compared to standard chow just as males did. However, female SNAP25Δ3/Δ3 mice display persistent metabolic protection even when housed at thermoneutrality. In this study, we investigate the mechanisms behind this sex dependent persistent phenotype. Thermoneutral set point did not differ between sexes nor genotype, suggesting that metabolic protection is not due to a difference in hypothalamic temperature regulation. Metabolic protection in SNAP25Δ3/Δ3 persisted in ovariectomized mice despite increased weight gain compared to mice receiving sham operations.ConclusionThis study has identified that there is not a sex-dependent difference for thermoneutral set point in mice. Additionally, there is a sex hormone independent mechanism driving the persistent metabolic protection of female SNAP25Δ3/Δ3 mice housed in thermoneutrality.